Increasing The Utilization of Technology And Economic Empowerment of The Maria Immaculata Lekebai Parish - Roberthus Gaga Nae; Valentin Romualda Gaudiosa Bella Adur; Yesita Madona Vikmart Mada Hekopung; Heldita Chaterina Kopa; Marieta Prasetia Osi Ndoi (Dinasti International Journal of Education Management and Social Science, 2025)
This community service program aims to increase the use of technology and empower the Catholic Youth (OMK) community at the Santa Maria Immaculata Lekebai Parish. This activity is motivated by the significant potential of young people in technology mastery and their strategic role in community economic development. Through intensive training, mentoring, and access to digital platforms, this program encourages OMK to develop skills in information technology and locally-based entrepreneurship. Implementation methods include a participatory approach, knowledge transfer, and hands-on practice in micro-enterprise management and digital marketing. The results of the activity demonstrate an increase in OMK members' understanding and ability to use technology productively and the growth of sustainable creative economic initiatives. This service program is expected to become a model for church-based youth community empowerment that is adaptive to current developments.